The Use of Jargon in Whatsapp Chatting by UKI Toraja Students - Resnita Dewi (Universitas Cokroaminoto Palopo, 2023)
This research aims to describe the forms of jargon used by WhatsApp users among students at the Toraja Christian University in Indonesia. This qualitative research relies on data collected from WhatsApp users among students at Toraja Christian University. The data is gathered through (1) reading techniques and (2) note-taking techniques. The results of this research indicate that, in terms of form, the jargon used by WhatsApp users among students at Toraja Christian University consists of four forms: basic word forms, abbreviation forms, phrase forms, and acronym forms.